Lipid Deterioration in Broiler Ration Containing Crude Palm Oil (CPO) with Addition of Garlic (Alium sativum) and Cumin (Cuminum cyminum Linn.) as Natural Antioxidant During the Storage - Yuli Retnani; D. Kurniawan; S. Yusawisana; L. Herawati (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2010)
One disadvantage of crude palm oil (CPO) as a feedstuff is its property of rapidly being rancid, and thus could decrease quality and palatability of ration. To over come the problem, an antioxidant is needed to prevent lipid deterioration. The aim of this research was to prevent lipid deterioration in broiler ration containing CPO using garlic and cumin as antioxidants. The experimental run in a factorial arrangement according to completely randomized design with 2 factors and 3 replications for each treatment combination. The first factors were either A1= control ration, A2= control ration + 0.2% garlic, A3= control ration + 0.4% garlic, A4= control ration + 0.6% garlic, A5= control ration + 0.02% BHT or B1= control ration, B2= control ration + 0.2% cumin, B3= control ration + 0.4% cumin, B4= control ration + 0.6% cumin, B5= control ration + 0.02% BHT. Butyl hidroksitoluena (BHT) is a synthetic antioxidant. The second factors were duration of storage, i.e. P1= 0 week, P2= 2 weeks, P3= 4 weeks. Parameters observed were water content, fat content and free fatty acid content of the ration. The results of the experiment indicated that use of both antioxidant garlic and cumin decreased (P<0.05) free fatty acid content and fat content, but the former did not affect water content as the later did. The best ration was ration containing either 0.6% garlic or 0.4% cumin as an antioxidant which was indicated by a decrease in free fatty acid and lipid contents so that could slow down lipid deterioration in the ration. Use of garlic 0.6% or cumin 0.4% was better compared with the use of BHT 0.02%. Results also indicated that storage time affected (P<0.01) parameters in terms of increasing water content, free fatty acid content, and decreasing fat content